The determinants of motherhood and work status: a survey - Daniela Del Boca; Marilena Locatelli (Institute for the Study of Labor (IZA), 2006)
In this paper we present important empirical evidence regarding recent trends in women's participation and fertility in European countries, and provide several interpretations of the differences across countries. Several recent analyses have considered labour supply and fertility as a joint decision and have explicitly taken into account the endogeneity of fertility in labour market participation decisions of women. We survey microeconomic analyses that explore the impact of social policies on the joint decisions of labor market participation and fertility. The results of most analyses indicate that social policies, taking into account several variables (family background, the allocation of time within the household, religion and culture), have a very relevant role in explaining different degrees of incompatibility between employment and child rearing across different countries. The incompatibilities between motherhood and careers find reconciliation in policies that enhance employment flexibility and diminish the potential opportunity costs of children.
urn:nbn:de:101:1-20090309147
Keywords: 330